Mapping Sea Ice Surface Topography in High Fidelity With ICESat‐2. Issue 21 (2nd November 2020) - Farrell, S. L.; Duncan, K.; Buckley, E. M.; Richter‐Menge, J.; Li, R.
Abstract: The Advanced Topographic Laser Altimeter System on Ice, Cloud and land Elevation Satellite 2 (ICESat‐2) offers a new remote sensing capability to measure complex sea ice surface topography. We demonstrate the retrieval of six sea ice parameters from ICESat‐2/Advanced Topographic Laser Altimeter System data: surface roughness, ridge height, ridge frequency, melt pond depth, floe size distribution, and lead frequency. Our results establish that these properties can be observed in high fidelity, across broad geographic regions and ice conditions. We resolve features as narrow as 7 m and achieve a vertical height precision of 0.01 m, representing a significant advance in resolution over previous satellite altimeters. ICESat‐2 employs a year‐round observation strategy spanning all seasons, across both the Arctic and Southern Oceans. Because of its higher resolution, coupled with the spatial and temporal extent of data acquisition, ICESat‐2 observations may be used to investigate time‐varying, dynamic, and thermodynamic sea ice processes. Plain Language Summary: The small footprint, high‐pulse repetition rate and six‐beam configuration of the Advanced Topographic Laser Altimeter System on ICESat‐2 deliver the highest‐fidelity measurements of sea ice surface topography ever obtained from a spaceborne platform. Since mid‐October 2018, ICESat‐2 has provided observations throughout the winter growth and summer melt seasons. We show that ICESat‐2 measurements can be used to derive a suite of important sea ice properties, including surface roughness, pressure ridge height and frequency, lead frequency, and floe size distribution in the Arctic. We also demonstrate the capability to detect individual melt ponds on multiyear sea ice, marking the first time summer melt features have been reliably detected from a space‐based altimeter. ICESat‐2 observations deliver unprecedented new details of several sea ice properties that will be transformational in understanding time‐varying polar processes, occurring both during the winter and summer seasons, under a range of ice conditions. Key Points: ICESat‐2 provides a new remote sensing capability to measure complex sea ice surface topography at m‐scale resolution, across all seasons We demonstrate approaches to retrieve six key sea ice parameters using ICESat‐2 laser altimeter height measurements ICESat‐2 observations may be used to investigate time‐varying sea ice processes, advancing forecasting and modeling efforts